(untitled) (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACT Surfactant injection is one of the methods to reduce the remaining oil in reservoir. This is done by injecting a surface active substance into reservoir until the tension of water-oil interface can be decreased. In order to make this process working optimally, an appropriate surfactant that fits the condition and formation of water and reservoir is needed. This research was aimed at getting the best design of production process of methyl ester sulfonate (MES) surfactant by using a continuous system of STFR (single tube falling film sufonation reactor) with SO3 gas reactant and formulating MES surfactant for its application on EOR. Process improvement resulted the best MES surfactant at treatment combination of dry air addition of 1.82 kg/hours and pH 8, sulfonation time of 3-4 hours and purification without methanol addition. The best MES-based surfactant formulation to be applied on EOR (carbonate field) was formula with MES surfactant composition of 0.3%, Na2CO3 of 0.3% and salinity level of 15,000 ppm. Keywords: sulfonation, methyl ester sulfonate (MES), optimal salinity, alkaline, MES- based formula